2021
DOI: 10.1016/j.jet.2020.105131
|View full text |Cite
|
Sign up to set email alerts
|

A unified characterization of the randomized strategy-proof rules

Abstract: This paper presents a unified characterization of the unanimous and strategy-proof random rules on a class of domains that are based on some prior ordering over the alternatives. It identifies a condition called top-richness so that, if a domain satisfies top-richness, then an RSCF on it is unanimous and strategy-proof if and only if it is a convex combination of tops-restricted min-max rules. Well-known domains like single-crossing, single-peaked, singledipped etc. satisfy top-richness. This paper also provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…An important observation of Theorems 1 and 2 is that every strategyproof and non-imposing SDS on the respective domains can be represented as a mixture of deterministic voting rules, each of which is strategyproof and non-imposing. This is sometimes called deterministic extreme point property and it is remarkable that many important domains satisfy this condition [40]. On one side, this shows that randomization does not lead to completely new strategyproof SDSs.…”
Section: Results For the Tie-breaking Condorcet Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…An important observation of Theorems 1 and 2 is that every strategyproof and non-imposing SDS on the respective domains can be represented as a mixture of deterministic voting rules, each of which is strategyproof and non-imposing. This is sometimes called deterministic extreme point property and it is remarkable that many important domains satisfy this condition [40]. On one side, this shows that randomization does not lead to completely new strategyproof SDSs.…”
Section: Results For the Tie-breaking Condorcet Domainmentioning
confidence: 99%
“…For instance, Ehlers et al [18] have shown the existence of attractive strategyproof SDSs on the domain of single-peaked preference profiles [see also 36,37]. The existence of strategyproof and non-imposing SDSs other than random dictatorships has also been investigated for a variety of other domains [34,35,40]. Following a more general approach, Chatterji et al [14] and Chatterji and Zeng [15] identify criteria for deciding whether a domain admits such SDSs.…”
Section: Related Workmentioning
confidence: 99%
“…Inspired by this, many works in the literature express RSCFs as convex combinations of DSCFs [27,26,28,25,29]. The Lemma 2 provides such a characterization of all the unanimous and strategy-proof RSCFs by proving that they are equivalent to random min-max rules.…”
Section: Extreme Point Characterization (Epc)mentioning
confidence: 99%
“…Almost all unanimous and weak elementary monotonic swap-LOBIC RBRs on the single-crossing domain are swap-LDSIC. Roy and Sadhukhan (2019) show that an RSCF on the single-crossing domain is unanimous and DSIC if and only if it is a tops-restricted probabilistic fixed ballot rules (TPFBRs). Moreover, Cho (2016) shows that every swap-LDSIC RSCF on the singlecrossing domain is DSIC.…”
Section: Single-dipped Domainsmentioning
confidence: 99%